2017
DOI: 10.1002/nbm.3876
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution hyperpolarized metabolic imaging of the rat heart using kt PCA and kt SPARSE

Abstract: The purpose of this work was to increase the resolution of hyperpolarized metabolic imaging of the rat heart with accelerated imaging using k–t principal component analysis (k–t PCA) and k–t compressed sensing (k–t SPARSE). Fully sampled in vivo datasets were acquired from six healthy rats after the injection of hyperpolarized [1‐13C]pyruvate. Data were retrospectively undersampled and reconstructed with either k–t PCA or k–t SPARSE. Errors of signal–time curves of pyruvate, lactate and bicarbonate were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Signal in the myocardial muscle was low but present, possibly displaying perfusion. To reduce partial volume effects, higher spatial resolution could be used as recently shown by Wespi et al In line with literature, [1‐ 13 C]acetate signal was observed when the imaging slice covered larger fractions of the chest muscle. [1‐ 13 C]acetylcarnitine signal appeared in a ring like shape, located in the area of myocardial muscle, a feature that could not be resolved by images obtained with directly polarized sodium [1‐ 13 C]acetate, because of coarser spatial resolution.…”
Section: Discussionsupporting
confidence: 57%
“…Signal in the myocardial muscle was low but present, possibly displaying perfusion. To reduce partial volume effects, higher spatial resolution could be used as recently shown by Wespi et al In line with literature, [1‐ 13 C]acetate signal was observed when the imaging slice covered larger fractions of the chest muscle. [1‐ 13 C]acetylcarnitine signal appeared in a ring like shape, located in the area of myocardial muscle, a feature that could not be resolved by images obtained with directly polarized sodium [1‐ 13 C]acetate, because of coarser spatial resolution.…”
Section: Discussionsupporting
confidence: 57%
“…Based on the results presented in the supporting information, the undersampled data were reconstructed with k-t SPARSE, which outperforms k-t PCA for small acquisition matrix sizes and moderate acceleration factors R . 29 A gradient echo-based readout was used similarly to work by Naresh et al 13 Although balanced steady state free precession (bSSFP) sequences could potentially offer improved contrast and sensitivity, 36 gradient-echo sequences offer a straightforward solution to map signal enhancement to CA concentration. In this study, the readout of each of the two slices was segmented over two consecutive heartbeats, resulting in an overall temporal footprint of 200-220 ms (depending on the heart rate).…”
Section: Discussionmentioning
confidence: 99%
“…A dual‐contrast, saturation‐recovery, gradient‐echo sequence with a Cartesian readout was used. The acquisition scheme was undersampled in both k y and time domain using a Poisson weighting . The net undersampling factor was R = 4 (resulting in a total acquisition of 16 phase‐encoding steps per slice per dynamic).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations